El laboratorio virtual con el soporte del simulador Interactive Physics en el bloque leyes del movimiento y su relación con el rendimiento académico de los estudiantes de bachillerato general unificado de la unidad educativa comunitaria intercultural bilingüe “Achullay”, cantón Guamote, periodo académico 2015-2016. - Guambo Naula, César Guillermo (2017)
A low academic performance of students in the subject of Physics was detected in Bilingual Intercultural Educational Unit "Achullay", The causes are focused on social and economic aspects, including geographical location; This investigation has as general objective to apply the Virtual Laboratory with the support of the simulator Interactive Physics in the block laws of the movement to surpass the Academic Performance of the students. The type of research is qualitative, with descriptive design, the methods used were Inductive, deductive and synthetic analytical methods. The data collection was based on the survey and the observation sheet; the population was 117 students of the first year of BGU of the Educational Unit "Achullay", the type of sampling is non-probabilistic of the intentional type considering 34 students. Descriptive statistics was applied to validate the results; the design and application of the alternative guideline was based on the principle of teaching, learning, which generated interest, individual and group participation through student’s creativity. It is concluded that the guide contributed to student’s attention throughout the learning process and became an active methodological strategy in the teaching of Physics, through the development of virtual practices and problems. As well as it promoted the skills of solving problems; finally it is recommended to perform the virtual practices to relate them with a real laboratory. Teachers and students are encouraged to use the Interactive Guide to raise new ideas; as well as a learning methodology in a real social and academic context.